(untitled) (Research, Society and Development, 2021)
The AA7075-T6 alloy is widely used in aviation due to its low weight characteristics and mechanical properties. To increase corrosion resistance, this alloy is generally protected by cladding and later anodized. Cladding coating, despite increasing the cost of the alloy, is necessary, as it allows the entire surface of the alloy to be anodized. Attempts to anodize AA7075-T6 alloys without cladding, showed that the precipitates region of the alloy is not anodized, originating cathode sites and, therefore, accelerating corrosion. Because of that, this work proposed anodizing in different electrolytes aiming the coating of the alloy precipitates by anodizing. For this purpose, AA7075-T6 aluminum samples were anodized in 0.3 M Oxalic Acid and 0.15 M Niobyl Oxalate with process variation. Anodized samples were evaluated for anodizing transients, morphology, cross section and corrosion resistance. Through the anodizing transients, it was possible to characterize that the samples anodized in 0.3 M of Oxalic Acid had a higher charge density than the samples anodized in 0.15 M of Niobyl Oxalate. All samples showed formation of pits and holes in the surface layer of the oxide film. Through analysis of the cross section by scanning electron microscopy (SEM), it was possible to verify that the unblasted samples obtained an oxide film of greater thickness than the samples that were pickled. However, it was not possible to state that the precipitates were covered.